Enhanced Thermoelectric Performance of SmBaCuFeO5+δ/Ag Composite Ceramics. Issue 4 (10th January 2016) - Zeng, Chengcheng; Butt, Sajid; Lin, Yuan‐Hua; Li, Ming; Nan, Ce‐Wen
Abstract : Polycrystalline SmBaCuFeO5+δ /Ag composite ceramics have been synthesized by a traditional ceramic processing method. Phase composition and microstructural analyses indicate that with the introduction of Ag additives, the second phases of copper oxides and Ag appear in these composite ceramic samples. The hole concentration and molibility can be enhanced greatly by the addition of Ag particles, which results in a large increase in the electrical conductivity. The thermal conductivity behaviors show that phonons can be scattered effectively by point defects and mesoscale grain boundaries, which remain a slight change in thermal conductivity. A maximum ZT value 0.047 has been achieved at 1023 K in the SmBaCuFeO5+δ /20 vol% Ag composite ceramic, and is about 16 times than the pure SmBaCuFeO5+δ sample. Our results reveal that Ag addition is an effective way to enhance the thermoelectric properties.